The Impact of the COVID-19 Pandemic on the Lives of People With Gender Dysphoria - Guadagnin, Fernanda; da Silva, Dhiordan Cardoso; Schwarz, Karine; Villas Bôas, Anna Paula; Lobato, Maria Inês Rodrigues (Frontiers in Public Health, 2022)
Objective: To analyze the impact on the psychological and social aspects caused by the COVID-19 pandemic in individuals diagnosed with Gender Dysphoria (GD). Methods: Google Forms inventory was sent via WhatsApp, including qualitative and quantitative questions evaluating three life dimensions denominated as Sociodemographic, Economic, and COVID-19 pandemic. It was applied in two periods: At the beginning of the pandemic (June-2020) (P1) and one year later (June-2021) (P2). The inventory also included questions about economic dimensions before the pandemic for individual comparison purposes (P0). 48 individuals (28 transsexual women, 20 transsexual men) participated in both periods. Results: 77.1% (n=37) lived in Rio Grande do Sul, 50.0% (n=24) refereed incomplete high school; Monthly Income increased significantly between the periods (P0) and (P1). Emergence aid approval was significantly higher in (P2), 56.3% (n=27), compared to (P1), 39.6% (n=19). A statistically significant difference was detected in the feeling of depression in the (P2) among the cases that requested Emergency Aid. Conclusion: The studied population presented deterioration regarding their condition of social vulnerability in relation to formal employment, access to health services, and mental health.